2020
DOI: 10.1038/s41467-020-16245-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of wild-type p53 promotes mutant p53-driven metastasis through acquisition of survival and tumor-initiating properties

Abstract: Missense-type mutant p53 plays a tumor-promoting role through gain-of-function (GOF) mechanism. In addition, the loss of wild-type TP53 through loss of heterozygosity (LOH) is widely found in cancer cells. However, malignant progression induced by cooperation of TP53 GOF mutation and LOH remains poorly understood. Here, we show that mouse intestinal tumors carrying Trp53 GOF mutation with LOH (AKTP M/LOH) are enriched in metastatic lesions when heterozygous Trp53 mutant cells (AKTP +/M) are transplanted. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Cancer metastasis is a pathological process in which malignant cells spread from a primary site to a different site within the host's body [45,46]. The degradation of ECM plays a pivotal role in the process of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer metastasis is a pathological process in which malignant cells spread from a primary site to a different site within the host's body [45,46]. The degradation of ECM plays a pivotal role in the process of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of driver mutations is understood to be responsible for the malignant progression of CRC 5 , and genome research has identified driver genes that are frequently mutated in CRC cells and are suspected of promoting each step of malignant progression 6,7 . Using genetic mouse models, we previously examined the link between specific combinations of driver mutations and each process of intestinal tumor progression, including submucosal invasion, epithelial mesenchymal transition (EMT)-like morphology, intravasation, and metastasis [8][9][10][11] . However, recent bioinformatics analyses have indicated that most driver mutations are accumulated in primary CRCs, suggesting that the metastasis process is not promoted by genetic alterations and subsequent clonal selection 12,13 .…”
mentioning
confidence: 99%
“…To answer this question, we performed spleen transplantation experiments using a recently established organoid transplantation model 8,11 . In this model, mouse intestinal tumor-derived organoids carry various combinations of genetic alterations in driver genes.…”
mentioning
confidence: 99%
“…Cancer metastasis is a pathological process which malignant cells spread from a primary site to a different site within the host's body [39,40]. The degradation of ECM plays a pivotal role in the process of metastasis.…”
Section: Discussionmentioning
confidence: 99%